2023
DOI: 10.48550/arxiv.2303.02660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SynthASpoof: Developing Face Presentation Attack Detection Based on Privacy-friendly Synthetic Data

Abstract: Recently, significant progress has been made in face presentation attack detection (PAD), which aims to secure face recognition systems against presentation attacks, owing to the availability of several face PAD datasets. However, all available datasets are based on privacy and legallysensitive authentic biometric data with a limited number of subjects. To target these legal and technical challenges, this work presents the first synthetic-based face PAD dataset, named SynthASpoof, as a large-scale PAD developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Slightly better results were achieved when trained on HQ-WMCA and tested on WMCA, achieving an HTER of 18.2%. In [46] the authors introduced a new dataset of PAs based on synthetic face images and demonstrated the feasibility of using synthetic data for PAD.…”
Section: Vulnerability Of Face Recognition To Presentation Attacksmentioning
confidence: 99%
“…Slightly better results were achieved when trained on HQ-WMCA and tested on WMCA, achieving an HTER of 18.2%. In [46] the authors introduced a new dataset of PAs based on synthetic face images and demonstrated the feasibility of using synthetic data for PAD.…”
Section: Vulnerability Of Face Recognition To Presentation Attacksmentioning
confidence: 99%